Hepatitits A epidemic (past and present) - Kozishkurt, E. V.; Sovirda, O. S. (Journal of Education, Health and Sport, 2018)
The intensity of hepatitis A epidemic process in the world varies significantly, and its incidence rate correlates with the sanitary-hygienic condition of individual territories. HA continues to be relevant due to the widespread, multifactorial conditions of transmission in territories with different socio-economic levels of development, as well as due to co-infection with hepatitis B and / or C viruses and the development of severe clinical forms of the disease in adults. The objective: to make retrospective comparative study of the manifestations of hepatitis A epidemic process in historical aspect (30 years) and in the modern period. Results. It was established that HA epidemic process intensity inOdessa region in 1978-1987. corresponded to territories with high endemicity. After a 30-year period (2008-2017) the prevalence of HA corresponds to the characteristics of territories with low endemicity which is confirmed by seroprevalence analysis of the population. The results of serological studies indicate that children under 10 years old have anti-HAV IgG in 22.26% of cases, the general group under 15 years old - in 20.31%, among adults under 30 years old - in 33.33 %, so in these days natural immunization occurs more often after 14 years. Among people over 30 years of age, seroprevalence for HAV reaches 86.25%. The issue of immunization of children at the local level according to epidemic indications and adults at risk can be considered in the area under study.